2000
DOI: 10.1091/mbc.11.5.1753
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Heat Shock Transcription Factor Changes Conformation in Response to Superoxide and Temperature

Abstract: In vitro DNA-binding assays demonstrate that the heat shock transcription factor (HSF) from the yeast Saccharomyces cerevisiae can adopt an altered conformation when stressed. This conformation, reflected in a change in electrophoretic mobility, requires that two HSF trimers be bound to DNA. Single trimers do not show this change, which appears to represent an alteration in the cooperative interactions between trimers. HSF isolated from stressed cells displays a higher propensity to adopt this altered conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…We have shown that the conformational change can be induced by heat or superoxide acting directly on HSF (Lee et al, 2000), which suggests that a direct role of hsp70 may not be required for the activation of the heat shock response. We therefore seek a model for the role of the hsp70 proteins that accommodates both our biochemical data and the genetic data.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We have shown that the conformational change can be induced by heat or superoxide acting directly on HSF (Lee et al, 2000), which suggests that a direct role of hsp70 may not be required for the activation of the heat shock response. We therefore seek a model for the role of the hsp70 proteins that accommodates both our biochemical data and the genetic data.…”
Section: Discussionmentioning
confidence: 94%
“…We have shown recently (Lee et al, 2000) that HSF undergoes a conformational change upon heat shock. This conformational change is detectable only in the context of two HSF trimers bound cooperatively to DNA.…”
Section: Hsf Complexes Do Not Dissociate Upon Superoxidestimulated Comentioning
confidence: 99%
See 2 more Smart Citations
“…[126][127][128] Animal and yeast Hsfs have been found to act as direct ROS sensors. 129) Although yeast Hsf was found to be post-translationally activated by O À 2 , 130) human and Drosophila Hsfs directly sensed H 2 O 2 and assembled into a homotrimer as an active form in a reversible and redox-regulated manner. 131,132) Two Cys residues, located within and near the DNAbinding domain, were shown to be essential for the formation of intermolecular disulfide bonds, trimerization, and the nuclear localization of human Hsf in response to heat and H 2 O 2 .…”
Section: Common and Source-/kind-specific Ros Signaling Pathwaysmentioning
confidence: 99%